1998
DOI: 10.1046/j.1440-1754.1998.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Paediatricians: Referral rates and speech pathology waiting lists

Abstract: The results have important implications for developing best practice models for improving referral processes and access to speech pathology services for children with communication disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…There are limited data available on the effects of waitlists or the effects a delay of service have for children with developmental disabilities. Keating et al (1998), however, described the greatest concerns reported by stake-holders regarding time spent on waitlists as (1) concerns with the delay in the onset of services considering the clear benefits associated with early intervention, (2) lost time in the window of childhood development, and (3) prolonged or exacerbated stress and uncertainty put on families during the waiting process.…”
Section: Barriers To Servicesmentioning
confidence: 99%
“…There are limited data available on the effects of waitlists or the effects a delay of service have for children with developmental disabilities. Keating et al (1998), however, described the greatest concerns reported by stake-holders regarding time spent on waitlists as (1) concerns with the delay in the onset of services considering the clear benefits associated with early intervention, (2) lost time in the window of childhood development, and (3) prolonged or exacerbated stress and uncertainty put on families during the waiting process.…”
Section: Barriers To Servicesmentioning
confidence: 99%
“…Workshop participants affirmed that long waits for CDR services were of significant concern to parents and providers alike in light of three main considerations: (1) the evidence for early intervention for children with special needs; (2) the time‐sensitive nature of the developmental period of childhood in relation to therapeutic interventions; 4 and (3) the expectation that prolonged waiting will add to stress and uncertainty among parents and family members of a child awaiting diagnostic, assessment, and rehabilitation services, given the evidence that coping and adaptation are enhanced when families receive information and support through early intervention programs 41,42 . Long wait lists may have a demoralizing effect on service providers, 7 and may act as a deterrent to physicians referring children for rehabilitation services 43 …”
Section: Stakeholder Views and Dialoguementioning
confidence: 99%
“…(Note that we use the term ‘rehabilitation’ to include services aimed at restoring function, as well as ‘habilitation’ services for children who may never have established various functional skills.) There is a high level of concern among parents and professionals about waiting for CDR services in Canada, the UK, 6,7 and other parts of the world, including Australia (M Wake, personal communication 2007) and South Africa (C Adnams, personal communication 2007); this concern is related to familiarity with evidence and opinion in favor of early intervention for affected children, anecdotal awareness that some children and families seem to wait for very long periods for developmental and rehabilitation services, and the perception that large variations in wait times exist between regions and jurisdictions.…”
mentioning
confidence: 99%
“…Along with personnel and service provider shortages, long wait lists are another barrier to timely services. Estimates for wait times among families and individuals across the lifespan with NDDs are few and far between; however, stakeholders repeatedly report dissatisfaction with long wait lists and access to services (Keating, Syrmis, Hamilton, and Mcmahon 1998). Timely access to high-quality services may improve quality of life for persons with NDDs and their families and thus is important.…”
mentioning
confidence: 99%